Media perception and trust among disaster survivors: Tsunami survivors' interaction with journalists, media exposure, and associations with trust in media and authorities - Englund, Liselotte; Bergh Johannesson, Kerstin; Arnberg, Filip K. (Frontiers in Public Health, 2022)
A critical part of disaster communication is media coverage in the interface of the afflicted, media, and authorities. One communication key is building trust. Disaster survivors encounter journalists in a high-stress context, but little is known about their perceptions of these interactions and the subsequent media exposure. The aim of this study is to explore how survivors 6 years after a major disaster perceived their encounters with journalists and exposure in the media, as well as their level of trust in the media, compared with government and authorities. Data were used from a longitudinal study of Swedish tourists, repatriated from the 2004 Indian Ocean tsunami, surveyed up to 6 years after the tsunami to assess posttraumatic stress (PTS) and effects on mental health. At 6 years after, the survey included questions about survivors' perceptions of journalist interactions (reported by n = 311), of their own media exposure (n = 177), and survivors' trust in media organizations and public authorities (n = 1,181). Tsunami survivors mainly perceived interactions with journalists as being professional. There were 14% who reported that the interactions were supportive and 17% that the interactions were a strain. Similarly, most participants had a neutral view concerning the subsequent media coverage or exposure, although 12% experienced media exposure as stressful and 12% reported that it had been involuntary. Finally, the survivors indicated higher confidence and trust in Swedish radio and TV as compared to the Swedish authorities, and the participants' level of trust in the media was associated with their perceptions of journalists, r = 0.34, p < 0.001, and media coverage, r = 0.47, p < 0.001. Disaster survivors mainly agreed with emotionally neutral statements about interacting with the media, the performance of journalists on site, and their own media exposure. Nonetheless, a substantial minority found the encounters and exposure to be negative, and the results suggest a link between personal experiences or perceptions and trust in the media.